The Influence of Ease of Use, Benefit, and Risk on the Decision to Adopt DANA E-Wallet Among Students at the Faculty of Islamic Economics and Business, UIN Madura - Nur Tilawatil Quran; Khotibul Umam; Fatati Nuryana (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
Digital financial technology adoption among students remains a critical area of inquiry, particularly regarding the factors that drive or hinder e-wallet usage decisions. This study examines the influence of ease of use, perceived benefits, and perceived risk on the decision to use the DANA e-wallet among students at the Faculty of Economics and Islamic Business, UIN Madura. This study used a quantitative causal research design, with a population of 1,662 students. A total of 94 respondents were selected through purposive sampling. Data were collected via online questionnaires and analyzed using multiple linear regression with SPSS 26. The results showed that ease of use does not significantly influence the decision to use DANA e-wallet, whereas perceived benefits and perceived risk each had a significant effect. Simultaneously, the three independent variables significantly influence usage decisions, with a coefficient of determination of 68.4%. Conversely, 31.6% of the variation was explained by elements not included among the variables analyzed in this study. The study contributes practical implications for e-wallet service providers, emphasizing the need to enhance functional benefits, improve interface usability, and strengthen user trust in digital transaction security. [Adopsi teknologi keuangan digital di kalangan mahasiswa tetap menjadi area penelitian yang penting, khususnya mengenai faktor-faktor yang mendorong atau menghambat keputusan penggunaan dompet elektronik. Studi ini meneliti pengaruh kemudahan penggunaan, manfaat yang dirasakan, dan risiko yang dirasakan terhadap keputusan penggunaan dompet elektronik DANA di kalangan mahasiswa Fakultas Ekonomi dan Bisnis Islam, UIN Madura. Penelitian ini menggunakan desain penelitian kausal kuantitatif, dengan populasi 1.662 mahasiswa. Sebanyak 94 responden dipilih melalui pengambilan sampel bertujuan. Data penelitian dikumpulkan melalui kuesioner daring dan dianalisis menggunakan regresi linier berganda dengan SPSS 26. Hasil penelitian menunjukkan bahwa kemudahan penggunaan tidak secara signifikan memengaruhi keputusan penggunaan dompet elektronik DANA, sedangkan manfaat yang dirasakan dan risiko yang dirasakan masing-masing memberikan pengaruh yang signifikan. Secara simultan, ketiga variabel independen tersebut secara signifikan memengaruhi keputusan penggunaan dompet elektronik DANA dengan koefisien determinasi sebesar 68,4%. Sebaliknya, 31,6% dari variasi tersebut dijelaskan oleh elemen-elemen yang tidak termasuk di antara variabel yang dianalisis dalam penelitian ini. Studi ini memberikan implikasi praktis bagi penyedia layanan dompet elektronik, menekankan perlunya meningkatkan manfaat fungsional, memperbaiki kemudahan penggunaan antarmuka, dan memperkuat kepercayaan pengguna terhadap keamanan transaksi digital.]